Pengembangan Media Pembelajaran Video Komik Terhadap Kemampuan Pemecahan Masalah pada Materi Kesebangunan di Kelas VII SMP Negeri 1 Belitang Hilir - Aisyah, Yosi; Oktaviana, Dwi; Haryadi, Rahman (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to produce learning media in the form of comic video learning media for problem-solving abilities in similarity material in class VII of SMP Negeri 1 Belitang Hilir. This research is a Research and Development (R&D) with research procedures using the ADDIE model. The subjects in this study consisted of experts (validators) and students (product trial subjects). The data collection technique in this study was an indirect communication technique with research instruments in the form of material expert validation sheets and media expert validation sheets and questionnaires. Based on the results of validation by material experts, a percentage of 89.52% was obtained with very valid criteria. The results of media expert validation obtained a percentage of 82.05% with valid criteria, the calculation of teacher response questionnaires obtained a practicality percentage of 97.65% with very practical criteria, the calculation of student response questionnaires obtained a practicality percentage of 88.19% with very practical criteria, and the posttest results obtained a percentage of effectiveness of 76.67% with effective criteria.